Key genes and potential drugs in age-related hearing loss: transcriptome analysis of cochlear hair cells in old mice: Key genes and potential drugs in age-related hearing loss - Yang, Xiaoran; Wang, Guihua; Liu, Weimin; Zhang, Jianmin; Deng, Bin; Li, Xuzhao; Wang, Li (Cellular and Molecular Biology, 2023)
This study aimed to dig new molecular mechanisms and medications for age-related hearing loss (ARHL or presbycusis) by extracting common results of publicly available datasets. Based on five datasets (GSE153882, GSE121856, GSE98070, GSE45026, and GSE98071) in studies of cochlear hair cells, we explored the interrelationships among presbycusis-related genes, including gene interactions, enrichment analysis, miRNA-mRNA matching pairs, and potential new drugs. Together, there were 25 common increased mRNAs. A total of 183 drugs can simultaneously target 11 of these mRNAs. In the interaction network, hub genes included: Cbln1, Prl, Mpp6 and Gh. Meanwhile, there were 74 common decreased mRNAs. The hub genes include Cdkn1a, Egr1, and Ctgf. After de-duplication, the 25 common increased mRNAs had 946 matched miRNAs, with 34 decreased ones; and the 74 decreased mRNAs had 1164 matched miRNAs, with 26 increased ones. Between the inhibitors of increased mRNAs and enhancers of decreased mRNAs, there were 26 common drugs. Besides, we discovered six key genes that may play a crucial role in the onset of presbycusis. In conclusion, by jointly analyzing multiple datasets, we found 25 common increased mRNAs (e.g., Cbln1, Prl, Mpp6 and Gh) and 74 common decreased mRNAs (Cdkn1a, Egr1, and Ctgf), as well as 34 potential therapeutic miRNAs and 26 pathogenic miRNAs, and three candidate drugs (calcitriol, diclofenac, and diethylstilbestrol). They may provide new targets and strategies for mechanistic and therapeutic studies in ARHL.